The Role of Profitability and Dividend Policy in Mediated and Moderate the Company Growth Relationship with Firm Value: (Case Study on Registered Insurance Sub-Sector Company On The Indonesia Stock Exchange Period 2015 – 2021) - Aditia, Septian; Ichwanudin, Wawan; Purbasari, Intan (Eastasouth Institute, 2024)
This study aims to determine the effect of Company Growth proxied by Earnings Growth (X) on Firm Value proxied by Price to Book Value (Y) through Profitability proxied by Return on Asset (Z) as a mediating variable and Dividend Policy proxied by Dividend Payout Ratio (M) as a moderating variable in Insurance Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2015 - 2021. The population used in this study were all Insurance Sub-Sector companies listed on the Indonesia Stock Exchange for the period 2015 - 2021. The sample of this study amounted to 11 companies from 14 total populations using purposive sampling method. The data analysis technique used in this research is Partial Least Square with the help of SmartPLS 3.0 software. The results of this study indicate that: (1) Company Growth has a positive and significant effect on Profitability, (2) Company Growth has no effect on Firm Value, (3) Profitability has a positive and significant effect on Firm Value, (4) Profitability is able to mediate the relationship between the effect of Company Growth on Firm Value, (5) Dividend Policy is unable to moderate the relationship between the effect of Company Growth on Firm Value.